Easy access to medium-sized lactones through metal carbene migratory insertion enabled 1,4-palladium shift - Yu, Yinghua (Nat Commun, 2020)
Reactions that efficiently construct medium-sized lactones are significant, as they overcome the unfavorable entropic factor and transannular interactions for ring closure, and the lactones produced are common structural motifs recurring in many biologically active compounds. Herein, we describe a valuable strategy for medium-sized lactone synthesis by accomplishing site-selective C–H bond functionalization via a palladium carbene migratory insertion enabled 1,4-palladium shift. The overall process achieves the formal dimerization of two readily available benzaldehyde derivatives, providing value-added products medium-sized lactones. Our method is amenable to late-stage modification of approved drugs and other complex molecules. Mechanistic studies including deuterium-labeling experiments and DFT calculation shed light on the reaction pathways.